Pigmented villonodular synovitis of the elbow in a 16-year-old student - Jerome, Terrence J.; Sankaran, Balu; Varghese, Mathew; Thomas, Simon; Thirumagal, S.K. (Archives of Medical Science, 2009)
We present a 16-year-old student with right elbow pigmentary villonodular synovitis. Clinical diagnosis, radiological features, MRI findings, biopsy results, management and follow-up are discussed.